2018
DOI: 10.1108/scm-10-2017-0319
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of supply and manufacturing risk and business performance: a Chinese manufacturing supply chain perspective

Abstract: Purpose-This study explores the importance and impact of supply and manufacturing risk management upon business performance within the context of Chinese manufacturing supply chains. Design/Methodology/Approach-A two phased multi-method approach was adopted, which included a survey questionnaire to practitioners in Chinese manufacturing supply chains followed by semi-structured interviews. The findings included 103 valid survey responses complemented by six semi-structured interviews. Findings-The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 80 publications
(158 reference statements)
8
79
0
Order By: Relevance
“…The quantity of SSM practices is large when all measurements are considered. In this way, firms must perceive which practice is highly significant and persuasive in SSM as the firm size is also considered as a primary factor affecting a business supply risk management (Kumar et al, 2018) and network resources (Huggins & Johnston, 2010) since large firms are found to have better data conveyance and perform better in utilizing information (Ellegaard, 2008), as compared with small enterprises (Raza et al, 2019;Raza & Majid, 2016). Therefore, this study argument grounded in the conception that SSM practices can amplify SCRM and NC linked with firm size, which, in turn, strengthens the path between SSM practices and SP.…”
Section: Firm Sizementioning
confidence: 99%
See 2 more Smart Citations
“…The quantity of SSM practices is large when all measurements are considered. In this way, firms must perceive which practice is highly significant and persuasive in SSM as the firm size is also considered as a primary factor affecting a business supply risk management (Kumar et al, 2018) and network resources (Huggins & Johnston, 2010) since large firms are found to have better data conveyance and perform better in utilizing information (Ellegaard, 2008), as compared with small enterprises (Raza et al, 2019;Raza & Majid, 2016). Therefore, this study argument grounded in the conception that SSM practices can amplify SCRM and NC linked with firm size, which, in turn, strengthens the path between SSM practices and SP.…”
Section: Firm Sizementioning
confidence: 99%
“…In search of the answer to this question, recent literature mainly paid attention to firm's social and green practices and technological adaptation strategies (Bai et al, 2012;Beske-Janssen et al, 2015;Chardine-Baumann & Botta-Genoulaz, 2014;Mårtensson & Westerberg, 2016;Paulraj, 2011;Rathore et al, 2020). Furthermore, supply management literature reveals that considerable attention has been paid to environmental, social, and economic performances (Hong et al, 2018;Kumar et al, 2018). Limited studies have been carried out on supply chain sustainability practices and performance outcomes (Hong et al, 2018;Kamble et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discriminant validity was established by comparing the AVE with maximum shared variance (MSV) for each construct. MSVs of the constructs were less than AVEs, providing evidence of discriminant validity (Kumar et al, 2018;Liu et al, 2018). Furthermore, bi-variate correlations were compared with the square root of AVE (Fornell & Larcker, 1981).…”
Section: Assessment Of Psychometric Propertiesmentioning
confidence: 99%
“…This phenomenon has led to increased interest in supply chain risk management (SCRM) to cope with complex supply chain. SCRM has received increased attention from researchers and practitioners because of the uncertainty and complexity facing supply chains (Kumar et al,2018). SCRM provides effective tools and practices which, aligned with the corporate strategy, mitigates the challenges created by uncertainty and complexity.…”
Section: Introductionmentioning
confidence: 99%